Symmetric cash flow-taxation and cross-border investments - Frank Kramer (Universität Bayreuth, Lehrstuhl Betriebswirtschaftslehre I: Finanzwirtschaft und Bankbetriebslehre, 2009)
The discussion about income versus consumption as the ideal tax base looks back on a long history. In recent years, the debate about income versus consumption as the better tax base reemerged in the United States (2002) and in Germany (2006). In view of the long history of the debate, it is surprising that still relatively little research has been done on crossborder-investments in a cash flow-tax system. The presented article tries to fill this gap. For the case of a harmonized introduction of symmetric cash flow-tax systems in several countries, rules are developed that could guarantee a systematic and feasible treatment of crossborder investments. Preference is given to the RF-base-cash flow-tax on the personal level without a separate company tax. As a result the presented article states, that a coordinated introduction of symmetric cash flow-tax systems in several neighboring countries could be possible. To guarantee the success of the reform, each country must be willing to commit to intensive cooperation in tax matters. A unilateral introduction of a cash flow-tax and the resulting clash of a consumption-based tax system with an income-based tax system - the socalled collision-case - will be addressed in a following paper. – – Die Frage, ob das Einkommen oder der Konsum die vorziehenswürdige Bemessungsgrundlage bildet, weist eine lange Tradition auf. In der jüngeren Vergangenheit erlebte die Frage angesichts neuer Reformvorschläge in den USA (2002) und in Deutschland (2006) eine Renaissance. Angesichts der langen Historie der Diskussion überrascht es, dass die steuerliche Behandlung grenzüberschreitender Investitionen in einem Cash-flow-Steuer-System bisher kaum untersucht wurde. Der vorliegende Artikel versucht diese Lücke zu schließen. Für den Fall der Einführung gleicher Cash-flow-Steuer-Systeme in allen Ländern (Harmoniefall) werden Regelungen entwickelt, die eine systematische und durchführbare Besteuerung grenzüberschreitender Investitionen sicherstellen. Als betrachtetes Cash-flow-Steuer-System wird eine RF-base-Cash-flow-Steuer auf persönlicher Ebene ohne eigenständige Besteuerung auf Unternehmungsebene herangezogen. Der vorliegenden Artikel kommt zum Ergebnis, dass eine koordinierte Einführung gleicher Cash-flow-Steuer-Systeme möglich ist. Voraussetzung dafür ist allerdings eine enge Kooperation der Länder in Steuerfragen. Die unilaterale Einführung eines Konsumsteuersystems in einem einzelnen Land und das daraus resultierende Zusammentreffen von Konsumsteuersystem und Einkommensteuersystem - der sog. Kollisionsfall - werden in einem folgenden Beitrag untersucht.
Keywords: H21; H25; H87; 330; Cash flow-tax; consumption tax; international taxation; cross-border investments